Analysis of the Emergence Black Lives Matter in United States: Critical Theory Analysis - Khaila Meisya Permana, Khaila Meisya Permana; Badrus Sholeh (Universitas Airlangga, 2025)
This study discusses how critical theory analyzes the birth of the Black Lives Matter social movement by black people in the United States. This movement stems from the long-standing anger and disappointment of black people in the United States. The peak of this racial discrimination occurred in the enforcement of law in 2013, where the perpetrator (white) was acquitted after killing two black people. Based on this incident, the BLM movement was born as a response to violence and legal inequality against black people. The Black Lives Matter movement in critical theory can be understood as the result of a normative agenda to fight for the rights of those oppressed by a hegemonic power. This study aims to provide a new perspective in analyzing the birth of social movements. Through critical theory with a qualitative approach, this study highlights the role of critical theory by focusing on how systems can create discrimination against a race and normative agendas in explaining the emergence of collective social movements. The results of this study show that discrimination against black people in the United States is not only caused by racial differences but also the result of the manifestation of a discriminatory international system. The existence of the BLM is an effort by society to break free from this discriminatory system. Keywords: Racial discrimination, critical theory, social movements, United State, Black Lives Matter.